2001
DOI: 10.1038/sj.bdj.4801068
|View full text |Cite
|
Sign up to set email alerts
|

The reasons for extraction of permanent teeth in Scotland: a 15-year follow-up study

Abstract: Caries and its sequelae remain the most important cause of tooth loss throughout adult life in Scotland and, therefore, caries prevention and maintenance of restorations are of great importance at all ages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
78
1
4

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(87 citation statements)
references
References 14 publications
4
78
1
4
Order By: Relevance
“…A recent statistical analysis by the Central Department of Statistics and Information of Saudi Arabia showed that more than 75% of the Saudi population is aged 0–39 years and that this young generation has benefited from preventive programs implemented by many dental schools and governmental hospitals 23. Although periodontal disease has been shown to be the second major reason for tooth extraction in many studies,14,18,20,24 the present study shows that extraction for orthodontic problems was the second major reason for tooth extraction among Saudis (Figure 2). These findings are similar to those of a study conducted in Jordan, and could be related to the increasing interest in esthetic considerations in the general population 25.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…A recent statistical analysis by the Central Department of Statistics and Information of Saudi Arabia showed that more than 75% of the Saudi population is aged 0–39 years and that this young generation has benefited from preventive programs implemented by many dental schools and governmental hospitals 23. Although periodontal disease has been shown to be the second major reason for tooth extraction in many studies,14,18,20,24 the present study shows that extraction for orthodontic problems was the second major reason for tooth extraction among Saudis (Figure 2). These findings are similar to those of a study conducted in Jordan, and could be related to the increasing interest in esthetic considerations in the general population 25.…”
Section: Discussionmentioning
confidence: 50%
“…The higher percentage of extractions in females may be due to their commitment to managing dental problems compared with males. The percentage of extraction of teeth due to caries in the literature ranges from 20% to 60% 13,14,17,18,20–22. A recent statistical analysis by the Central Department of Statistics and Information of Saudi Arabia showed that more than 75% of the Saudi population is aged 0–39 years and that this young generation has benefited from preventive programs implemented by many dental schools and governmental hospitals 23.…”
Section: Discussionmentioning
confidence: 99%
“…Severe periodontitis that occurs in 8.5% of US and 11% of worldwide adult humans, (Kassebaum et al, 2014; Thornton-Evans et al, 2013), remains one of the two major causes for tooth extraction in the many adults who forego preventive dental care (Petersen, 2008). 20–42% of teeth extracted worldwide in adults are periodontally-involved (McCaul, Jenkins, & Kay, 2001; Aida et al, 2006; Vignarajah, 1993; Ong, Yeo, & Bhole, 1996; Reich & Hiller, 1993). The high prevalence of SP in humans emphasizes the potential value of preclinical models of human SP.…”
Section: Discussionmentioning
confidence: 99%
“…It is estimated that between 30 and 35% of all tooth extractions are due to periodontitis, while approximately one-half are the result of dental caries [1]. Since the association between tooth extraction and dental caries has been shown to considerably vary with age [29], assessing the presence of periodontal disease by extent of tooth loss alone may be inadequate to examine the link between periodontal disease and cancer; studies in this area may, however, provide some insights into the overall role of oral health in relation to malignant neoplasms. If clinical exams are not feasible, or are not carried out in a standardized manner, measures such as reported history of periodontal disease, self-reported tooth loss due to periodontal disease, or bitewing radiographs may provide a better assessment of the presence of periodontal disease.…”
Section: Review Of Epidemiologic Literaturementioning
confidence: 99%